THE ROLE OF INTERACTIVE CONTROL SYSTEMS IN STRENGTHENING ESG PRACTICES AND INVESTMENT EFFICIENCY: MCS-LOC INSIGHTS - Anis, Idrianita; Arsjah, Regina Jansen; Hartini, Hartini (UI Scholars Hub, 2024)
This research aims to develop an Environmental, Social, and Governance (ESG) practices model and index based on sustainable finance regulation from a Management Control System Four Levers of Control (MCS-LoC) perspective. The ESG index was developed by utilizing content analysis of information disclosure in annual and sustainability reports of ten non-financial industry sectors listed in the Indonesia Stock Exchange from 2015 to 2022 (640 observations). Subsequently, the effect of the ESG Index on Investment Efficiency (IE) was tested with the moderating role of Interactive Control (INTR). The results indicate that companies are in the second stage of the sustainable business transition, characterized by initiatives to formulate strategies and risk governance. ESG practices do not affect IE, but there is a moderating role (strengthening) of INTR in the general scenario. Additionally, INTR moderates the effect of Belief Systems but does not moderate the influence of Boundary Systems on IE. Conversely, Diagnostics Control negatively moderates (weakening) in the underinvestment scenario. In the overinvestment scenario, INTR negatively moderates the relationship between ESG practices and IE. This research successfully demonstrates the transformative potential of MCS-LoC in ESG practices and can enhance IE. The findings have practical implications for the non-financial industry and provide input for regulators.